Measurement of the tt̄ production cross section in pp collisions at √s=7 TeV using the kinematic properties of events with leptons and jets - The, C; Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; et al. (2011)
A measurement of the tt̄ production cross section in proton-proton collisions at a centre-of-mass energy of 7 TeV has been performed at the LHC with the CMS detector. The analysis uses a data sample corresponding to an integrated luminosity of 36 pb-1 and is based on the reconstruction of the final state with one isolated, high transverse-momentum electron or muon and three or more hadronic jets. The kinematic properties of the events are used to separate the tt̄ signal from W+jets and QCD multijet background events. The measured cross section is 173+39-32(stat. + syst.) pb, consistent with standard model expectations. © 2011 CERN for the benefit of the CMS collaboration.